A review on chitosan: a new solution for combating abiotic stresses in agriculture - P. Dongare, Prajwal; R. Shingote, Prashant; D. Parlawar, Narsing (Kongunadu Research Journal, 2020)
Chitosan is a second most abundant naturally occurring polysaccharide after cellulose derived from chitin which commercially produced from seafood shells, fungi (Aspergillus and mucus) and also from algae by alkaline deacetylation of chitin. It is bio adhesive, biocompatible, biodegradable, organic molecule. Chitosan has wide spread application in agriculture. Chitosan acts as bio-stimulant which upon application to plants stimulates photosynthetic rate, enhances antioxidant production, increases tolerance to biotic and abiotic stresses. Chitosan causes hydrolysis of peptidoglycan of microbes resulting to death of microbes. Recent studies have shown that chitosan induces mechanisms in plants against various biotic and abiotic stresses and helps in formation of barriers that enhances plant's productivity.This paper takes a closer look at the genesis, structural alteration and physiological responses of chitosan foliar applications on plants.As, Abiotic stresses is an important multidimensional environment stresses that damage plant’s physiology, biochemical propertIes and Molecular traits. Chitosan help to combat abiotic and biotic stresses.